Into the Breach : Samuel Beckett and the Ends of Literature - Trezise, Thomas (Book collections on Project MUSE., 2014)
Arguing that Beckett's understanding of subjectivity cannot be reduced to that of phenomenology or existential humanism, Thomas Trezise offers a major reinterpretation of Beckett in light of Freud and such post-modernists as Bataille, Blanchot, and Derrida. Through extended comparisons of Beckett's trilogy of novels with the writings of these thinkers, he emphasizes a ""general economy"" of signification that both produces and dispossesses the phenomenological self. Trezise shows how Beckett's work defines literature as an instance within this economy and in so doing challenges traditional